Personal Names of the Pentateuch in the Northwest Semitic Context: A Comparative Study. Issue 1 (2nd January 2019) - Rahkonen, Pauli
ABSTRACT: The personal names of the Pentateuch (the first 11 chapters excluded) have not very often been under systematic scientific investigations. The topic is interesting from the points of view of linguistics, onomastics, theology and ethnohistory. The anthroponyms of the Pentateuch are compared with personal names found from the 2 nd millennium BCE (from Amorite, Ugaritic and Amarna Canaanite sources) and with anthroponyms from extrabiblical and biblical Hebrew sources, as well as with Phoenician sources of the first half of the 1 st millennium. The conclusion is that the anthroponyms of the Pentateuch reflect the onomasticon of the second millennium, having slightly modified typological and lexical roots in the same Northwest Semitic entity as Amorite, Amarna Canaanite and Ugaritic personal names.